A Comprehensive Review on Graphene Nanoparticles: Preparation, Properties, and Applications - Yusaf T.; Mahamude A.S.F.; Farhana K.; Harun W.S.W.; Kadirgama K.; Ramasamy D.; Kamarulzaman M.K.; Subramonian S.; Hall S.; Dhahad H.A. (MDPI, 2023)
nanoparticle